Human development III: Bridging Brain-Mind and Body-Mind. Introduction to “Deep” (Fractal, Poly-Ray) Cosmology - Søren Ventegodt; Tyge Dahl Hermansen; Erik Rald; Trine Flensborg-Madsen; Maj Lyck Nielsen; Birgitte Clausen; Joav Merrick (The Scientific World Journal)
Reality can be interpreted in many ways, but two distinctly different ways are the mental and the emotional interpretation. The traditional way of thinking in science today is the first: an often simple and mechanical interpretation of reality that empowers us to handle the outer physical world with great, often brutal efficiency. The development of a mind that enables us to handle the outer physical world and survive makes a lot of sense from an evolutionary perspective; the problem is that the mental reason and linear logic reduces all phenomena to well-defined interacting objects, which might not exist from a deeper perspective of reality. A more intuitive way to interpret the world makes much more sense, when it comes to our human relations. So to function as a human being, we need both these two ways of seeing the world, and two different modi operandi. In many patients, we find an internalized conflict between logical and mental reasoning on one hand, and emotional and sexual approach to reality and human needs on the other. We speculate that this conflict causes the deep emotional problems that really are the basis of most human diseases. Only by merging brain-mind and body-mind will we be whole and free and truly ourselves. We need to develop our mental understanding, deepen our cosmology, and develop our sexuality and body-mind in order to make them meet and merge. To facilitate this existential healing, we propose a third integrative way of looking at our human nature, which we call “the energetic-informational interpretation of reality”. What it does is allows us to look at both brain-mind and body-mind as a highly structured field of “energy and information”. Energy and information are actually the same from a scientific point of view; when the world is seen through the body-mind, it looks more like energy; when seen though the brain-mind, it looks more like information.